Effective Potential for Magnetic Resonance Measurements of Restricted Diffusion - Özarslan, Evren; Yolcu, Cem; Herberthson, Magnus; Westin, Carl-Fredrik; Knutsson, Hans (Frontiers in Physics, 2017)
The signature of diffusive motion on the NMR signal has been exploited to characterize the mesoscopic structure of specimens in numerous applications. For compartmentalized specimens comprising isolated subdomains, a representation of individual pores is necessary for describing restricted diffusion within them. When gradient waveforms with long pulse durations are employed, a quadratic potential profile is identified as an effective energy landscape for restricted diffusion. The dependence of the stochastic effective force on the center-of-mass position is indeed found to be approximately linear (Hookean) for restricted diffusion even when the walls are sticky. We outline the theoretical basis and practical advantages of our picture involving effective potentials.